Evaluasi Pendapatan Dan Belanja Desa (Apbdesa) Desa Sungai Pura Kecamatan Air Besi Kabupaten Bengkulu Utara - Lorita, Evi; Amin, Bando; Oktaviani, Zanatha Cerisilia (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
This study aims to evaluate the accountability of the management of the Village Revenue and Expenditure Budget (APBDesa) in Sungai Pura Village, Air Besi Sub-district, North Bengkulu Regency. The research focuses on three dimensions of accountability: financial accountability, benefit accountability, and procedural accountability, as formulated by Mahsum et al. (2004). The study employs a descriptive qualitative method with data collected through in-depth interviews, observation, documentation, and triangulation. The main informants include the village head, village treasurer, and head of the Village Consultative Body (BPD), while supporting informants are community members, youth leaders, and religious figures. The findings reveal that, in general, the management of APBDesa in Sungai Pura Village complies with the principles of accountability. Financial accountability is reflected in the preparation and publication of regular financial reports. Benefit accountability is evident in the effective use of village funds for infrastructure projects that benefit the local community, such as the construction of Posyandu and retaining walls. However, procedural accountability remains an issue, especially due to the limited community involvement in village deliberations and the lengthy and complex administrative process for fund disbursement. The study recommends enhancing community participation in the planning and monitoring of APBDesa, as well as simplifying the bureaucratic procedures for fund disbursement. These findings are expected to provide useful input for village governments in improving transparent and participatory financial management.